LINC00963 Confers Oncogenic Properties in Glioma by Regulating the miR-506/BCAT1 Axis - Ye, Feng; Xu, Ronghua; Ge, Yuanhong; Zheng, Yi; Liu, Xiaowei; Deng, Pingfu; Xu, Xuejun (Cancer management and research, 2020)
Glioma is a prevalent disease of the central nervous system with a high incidence and mortality rate. Many long noncoding RNAs (lncRNAs) have been determined to be critical regulators of glioma oncogenesis. However, the function and mechanism of LINC00963 in glioma have not been fully elucidated. The expression level of RNA was determined by qRT-PCR, and the protein level was determined by Western blot analysis. A luciferase activity assay was conducted to verify the interaction between miRNA and lncRNA or the target gene. The proliferation, cell cycle distribution, invasion, and migration were evaluated by MTT, EdU, flow cytometry, wound-healing and Transwell invasion assays, respectively. In vivo tumor growth was evaluated in a xenograft nude mouse model. We found that LINC00963 was upregulated in glioma cells and tissues and associated with the poor prognosis of patients with glioma. Ectopic expression of LINC00963 promoted cell proliferation, cell cycle progression, migration, and invasion in vitro and tumorigenesis in vivo. Mechanistically, the results of luciferase activity and RNA pulldown assays validated that LINC00963 could act as a molecular sponge of miR-506. Reciprocal repression was found between LINC00963 and miR-506. In addition, BCAT1 was identified as a target of miR-506, and both the mRNA and protein levels of BCAT1 were reduced by miR-506. In tumor tissues, the expression of BCAT1 was negatively and positively correlated with miR-506 and LINC00963 expression, respectively. The reintroduction of BCAT1 in glioma cells abolished the tumor suppressive function of miR-506 by promoting cell viability and motility. The upregulated LINC00963 and BCAT1 were associated with the aggressive phenotypes of tumors. Our data revealed that LINC00963 confers oncogenic function in the progression of glioma and that the LINC00963/miR-506/BCAT1 axis may be a novel mechanism and therapeutic strategy for this disease.